2022
DOI: 10.1016/j.jseint.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transdermal 4% lidocaine patches for postoperative pain management after arthroscopic rotator cuff repair: a prospective trial

Abstract: Background Postoperative pain management continues to be a challenging aspect of patient care. Lidocaine patches have shown efficacy in reducing pain in other surgical specialties and mixed results in orthopedic trials. We sought to determine the effectiveness of nonprescription lidocaine patches in reducing postoperative pain after arthroscopic rotator cuff repair Methods Patients undergoing primary arthroscopic rotator cuff repair were recruited from 3 surgeons at a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Therefore, we extracted and analyzed the pain scores at 12, 24, and 48 hours after the operation. Five trials recorded postoperative pain scores at 12 hours, 12,14,23,25,26 10 trials recorded postoperative pain scores at 24 hours, 12–14,17,21–26 and 5 trials recorded postoperative pain scores at 48 hours 13,16,22,23,25 . The analysis indicated that pain scores in the lidocaine patch groups were significantly lower (MD=−1.32 [95% CI, −1.96 to −0.68], P <0.0001; I 2 =92%) at 12 hours after the operation (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, we extracted and analyzed the pain scores at 12, 24, and 48 hours after the operation. Five trials recorded postoperative pain scores at 12 hours, 12,14,23,25,26 10 trials recorded postoperative pain scores at 24 hours, 12–14,17,21–26 and 5 trials recorded postoperative pain scores at 48 hours 13,16,22,23,25 . The analysis indicated that pain scores in the lidocaine patch groups were significantly lower (MD=−1.32 [95% CI, −1.96 to −0.68], P <0.0001; I 2 =92%) at 12 hours after the operation (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…A total of 140 studies (PubMed 43, Cochran 71, and Embase 26) were retrieved. After screening, 16 randomized controlled trials (RCTs) were included 12–14,16–28 . The data from 918 patients were obtained, of which 462 patients used lidocaine patches, and 456 patients did not use patches or used blank patches.…”
Section: Resultsmentioning
confidence: 99%
“…This study found no signifi-cant difference in pain scores or opioid consumption between the lidocaine group and the control group. Furthermore, patients in the lidocaine group were less satisfied with their pain control between postoperative days 2 and 8 23 .…”
Section: Other Interventionsmentioning
confidence: 92%
“…Four studies (19.0%) assessed local pain management modalities, such as transcutaneous electrical nerve stimulation (TENS), cryotherapy, or bandaging 18,22,25,34 . One study each (4.8%) evaluated topical treatment (lidocaine gel patch) 23 and relaxation therapy 27 .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation